Riofrío, J.C. & Marín Sevilla, M. (2012). Régimen de competencia. Quito: CEP - Danilo Icaza Ortiz (Universidad Hemisferios, 2012)
This paper is a review of the competition regime works of various authors, published under the auspices of the University of the Hemispheres and the Corporation for Studies and Publications. Analyzes the structure, the general concepts, case law taken for development. Includes comments on the usefulness of this work for the study of competition law and the contribution to the lawyers who want to practice in this branch of economic law.